Transformasi Kepemimpinan Ethical dalam Manajemen Pendidikan Islam di Madrasah - Anggini, Niken Lufi; Khaudli, Muh. Imam; Aimah, Siti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to provide a deeper understanding of about how ethical leadership in Islamic education management in madrasah. The method in this study uses qualitative methods at MTs Al Amiriyyah Blokagung Banyuwangi. This research design uses qualitative research with a case study approach. Qualitative research with a case study approach. The sources of information in the research are the Principal, Teachers and Students. This data collection technique uses observation, interviews, and documentation. This data analysis uses data collection data collection, data reduction and categorization, data appearance and conclusion drawing. The results in this study that the transformation of ethical leadership in Islamic education management in madrasah through the Development of Work Ethic and Professionalism of Teachers, Development of Social and Emotional Skills of Students and Improvement of Madrasah Image and Reputation. development of work ethic and professionalism of teachers with Commitment to Duty, Teaching Quality, Self-Development, Discipline and Work Ethics, Involvement in the School Community, Self Evaluation and Reflection, Cooperation and Collaboration, and Adaptability and Innovation. The development of social and emotional skills is realized through extracurricular programs. Improving the image and reputation of a madrasah is key in attracting prospective students, gaining community support, and building strong trust.